SÍNDROME DE BURNOUT E A DOCÊNCIA NO ENSINO BÁSICO: UMA ANÁLISE COMPARATIVA ENTRE DOCENTES DE ESCOLAS PÚBLICAS E PRIVADAS. - SANTANA, Gracielle dos Santos (2021)
Burnout Syndrome is a professional syndrome represented by the individual's physical and emotional exhaustion and affects workers who work in direct contact with the public. This Syndrome has three dimensions characterized as Emotional Exhaustion, which causes the individual to feel extremely tired; Depersonalization, manifested by behaviors of indifference to the public it serves and low Professional Fulfillment, evidenced by the loss of interest in the activity they perform and lack of professional perspective. In the current context, the teaching category of basic education is seen as one of the most affected by Burnout Syndrome, in this sense it is relevant to understand what the repercussions may be for the health and work of these professionals. Thus, this research had as general objective to understand the conditions and organization of work that contribute to the manifestation of symptoms and development of Burnout Syndrome in teachers of basic education in public and private schools in São Luís/MA. Therefore, we sought to understand the Burnout Syndrome and its perception among teachers in the labor context; analyze the work process and its impact on the health of teachers; identify coping strategies used by teachers for the symptoms of Burnout Syndrome and describe the professional experiences related to the manifestation of Burnout Syndrome in teachers. We used the Work Psychology framework, as well as studies that discussed the Burnout Syndrome and how it manifests in different professionals. Data were collected through exploratory research of a basic nature, applying the Maslach Burnout Inventory to 41 participants, teachers from public and private schools, and a structured interview was conducted with 4 participants who indicated that they were affected by Burnout Syndrome, through of the inventory. The data obtained from the inventory were analyzed using the SPSS software and the interview was based on Bardin's content analysis. The results of the inventory showed that public school teachers have a higher score in Emotional Exhaustion and a lower score in low Professional Achievement, and private school teachers have greater Depersonalization, which are indicative dimensions of Burnout Syndrome. Through the interview, it was observed that the structural problems contribute to the intensification of the suffering experiences of public school teachers, while the pressures and high hours have a more significant impact on private school teachers. Both segments use strategies to deal with the syndrome symptoms, these being the removal of work-related activities, focusing on self-centered tasks and rest. In this sense, it was evident that both contexts bring repercussions to the health of teachers and that the Burnout Syndrome needs to be increasingly clarified for teachers, so that they can make use of resources to prevent and deal with illness.